Building the foundation for successful collaboration and partnerships - "Hey .... you're not so bad pardner!" - Rogers, Rox, author (Colorado State University. Libraries, 2009)
Presentation discusses the partnership between Partners for Fish and Wildlife Program, Mountain-Prairie Region and private landowners and the Partner's program cornerstones for a successful partnership. Based upon the Partner's program the presenter discusses how to develop a successful collaboration.
Presented at the Bridging the gap: collaborative conservation from the ground up conference, September 8-11, 2009, Colorado State University, Fort Collins, Colorado, sponsored by the Center for Collaborative Conservation, https://collaborativeconservation.org/. This conference brought together people with experience working collaboratively to achieve both conservation and livelihood goals in tribal nations, rangelands, forests, watersheds, agricultural lands, and urban areas.
Christoffersen is the executive director for Wallowa Resources. He has a bachelor's in Economics from Williams, and a Masters in Forestry from Oxford University. His work experience includes six years in eastern and southern Africa on forestry and wildlife management issues, with an emphasis on community-based natural resource management. Previously, Christoffersen has served as executive director for the U.S. Office of Africa Resources Trust and regional program coordinator for the IUCN Regional Office in Southern Africa. Other work includes policy work with the European Commission on matters related to CITES and natural resource management, and short-term field work in Australia (livestock), U.K. (forestry), Norway (forestry and fishing), and Israel (agriculture). Since working in Oregon, Christoffersen has served on the National Commission on Science for Sustainable Forestry and he chaired the Governor of Oregon's Eastside Forest Advisory Panel from 2003 to 2005.
PowerPoint presention
Keywords: leadership; community-based conservation; collaborative conservation; strategies